PENGARUH INFLUENCER MARKETING DAN ONLINE CUSTOMER REVIEW MELALUI SOCIAL MEDIA TERHADAP KEPUTUSAN PEMBELIAN PRODUK FOCALLURE PADA GENERASI Z - Amelia, Mita; Hadita, Hadita; Winarso, Widi (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
The aim of this research is to measure the extent of influence of influencer marketing and online customer reviews on purchasing decisions for Focallure products among Generation Z via social media. The research method used is a quantitative method by distributing questionnaires to respondents. The data analysis technique in this research uses Structural Equation Modeling Partial Least Square (SEM-PLS) analysis with the help of SmartPLS version 4.0 software. The research results show that influencer marketing and online customer reviews have a significant influence on purchasing decisions, social media has a significant influence on purchasing decisions, and influencer marketing and online customer reviews via social media have an indirect and significant influence on purchasing decisions